Chest-wall simulator - Ferreira, João Pedro Linhares (2021)
Monitoring vital signs, especially respiration and heartbeat, helps prevent and detect conditions that can put the patient's well-being at risk. In the last few years, there has been a considerable evolution in wireless vital signs detection methods especially in radar technology based on the advances in antenna technologies and digital signal processing. One of the most promising methods to acquire the aforementioned vital signs is the Frequency-Modulated Continuous-Wave (FMCW) radars. However, in spite of the constant development, the results obtained by these type of radars are still affected by several factors such as the unattended person movements that can compromise the correct extraction of the vital signs such as the respiratory rate and the heart rate. This dissertation presents a system capable of emulating the chest-wall motion by using an linear actuator with a built-in step-motor. Experimental results using a plastic optical fiber sensor, capable of discriminate linear motions at a micro level, and a FMCW radar developed by Texas Instruments prove that the system is reliable and can act as substitute of a person.